2020
DOI: 10.11609/jott.4552.12.10.16239-16244
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and morphotype diversity of Trichuris species and other soil-transmitted helminths in captive non-human primates in northern Nigeria

Abstract: A study to determine the prevalence and morphotype diversity of soil-transmitted helminths in captive non-human primates (NHPs) in northern Nigeria was conducted.  Simple flotation and sedimentation methods were used to examine fecal samples. A Morphometric analysis was done on Trichuris spp. eggs to determine the diversity of whipworm circulating in NHPs in the study area.  High prevalence (60%) of infection was recorded in captive NHPs; Patas Monkey (n=17), Tantalus Monkey (n=9), Mona Monkey (n=7), Vervet Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Other studies have found multiple morphotypes of Trichuris sp. in nonhuman primate hosts in captivity in Nigeria [74,75], suggesting that potentially multiple species of Trichuris sp. may infect nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found multiple morphotypes of Trichuris sp. in nonhuman primate hosts in captivity in Nigeria [74,75], suggesting that potentially multiple species of Trichuris sp. may infect nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found multiple morphotypes of Trichuris sp. in nonhuman primate hosts in captivity in Nigeria [74,75], suggesting that potentially multiple species of Trichuris sp. may infect nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found multiple morphotypes of Trichuris sp. in nonhuman primate hosts in captivity in Nigeria [74,75], suggesting that potentially multiple species of Trichuris sp. may infect nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%